1996
DOI: 10.4141/cjss96-028
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil management systems on organic dwarf apple orchards and soil aggregate stability, bulk density, temperature and water content

Abstract: With growing pressure to reduce pesticide use, fruit growers require an alternative to herbicidal control of weeds. One option is the use of mulches or permanent vegetative ground covers, which in turn may have advantages in promoting soil physical properties and improving growth. This study examined the short-term effects of ground cover management in two newly established dwarf apple orchards in Quebec. Effects of cultivation, composted manure mulch, straw mulch, grass cover crops, a cover crop mixture of lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 12 publications
3
35
0
1
Order By: Relevance
“…Bhardwaj and Kumar (2012) reported that black polythene mulch acts as an insulating barrier, which checks evaporation from soil surface and conserves soil moisture. Similar findings were obtained by several researchers (Walsh et al, 1996 andChandel et al, 2010) who reported comparatively higher soil moisture contents in different mulches over unmulched trees.…”
Section: Soil Moisturesupporting
confidence: 80%
See 1 more Smart Citation
“…Bhardwaj and Kumar (2012) reported that black polythene mulch acts as an insulating barrier, which checks evaporation from soil surface and conserves soil moisture. Similar findings were obtained by several researchers (Walsh et al, 1996 andChandel et al, 2010) who reported comparatively higher soil moisture contents in different mulches over unmulched trees.…”
Section: Soil Moisturesupporting
confidence: 80%
“…Various workers Kathiravan, 2009 andLiu et al, 2014) also found an increase in soil temperature with polythene and straw mulches. Walsh et al, (1996) found higher soil temperature under cultivation as compared to straw mulch in apple. Mulches reduces the temperature fluctuation at night, condensation on the underside of the mulch absorbs the long wave radiation emitted by the soil thereby slowing cooling of the soil.…”
Section: Soil Temperaturementioning
confidence: 99%
“…O manejo adequado da cobertura pode proporcionar melhoria de atributos físicos, químicos e biológicos do solo (Medeiros, 1992;Neves et al, 2006), o que auxilia na produção das fruteiras (Ragozo et al, 2006), merecendo especial atenção em sistemas de produção orgânica (Walsh et al, 1996;Goh et al, 2000).…”
Section: Introductionunclassified
“…The high yield in apple production is facilitated by cultivation of dwarf varieties, which lowers the maintenance costs due to pruning, harvesting, and applying pesticides and herbicides, in addition to increasing the nutrient uptake of roots (DPT, 2006). Moreover, dwarf apple trees come into bearing 2-3 years after planting, and therefore provide an income more rapidly than standard trees (Walsh et al, 1996). Thus, apple is a promising commercial crop, particularly in regions with low income and fragmented lands.…”
Section: Introductionmentioning
confidence: 99%